2020
DOI: 10.1136/sextrans-2020-054660
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive account of 18 adults with known HIV infection hospitalised with SARS-CoV-2 infection

Abstract: ObjectiveTo report on the clinical characteristics and outcome of 18 people living with HIV (PLWH) hospitalised with SARS-CoV-2 infection in a London teaching hospital.MethodsThe hospital notes of 18 PLWH hospitalised with SARS-CoV-2 infection were retrospectively reviewed alongside data concerning their HIV demographics from an established HIV Database.ResultsThe majority (16/18) had positive PCR swabs for SARS-CoV-2, and two had negative swabs but typical COVID-19 imaging and history. Most were male (14/18, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In International Journal of Infectious Diseases , Wang et al have recently reported a case of one HIV/COVID-19 patient with low CD4 + count who had a longer COVID-19 course and lower antibody amount ( Wang et al, 2020 ). Further, it has been detected that HIV/SARS-CoV-2 co-infection may lead to pneumonia complications oftener than COVID-19 itself ( Madge et al, 2020 , Okoh et al, 2020 ). The ability of HIV/SARS-CoV-2 co-infection to cause excessive T cell activation has been observed in sample sets little in size ( D’Ettorre et al, 2020 , Gao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In International Journal of Infectious Diseases , Wang et al have recently reported a case of one HIV/COVID-19 patient with low CD4 + count who had a longer COVID-19 course and lower antibody amount ( Wang et al, 2020 ). Further, it has been detected that HIV/SARS-CoV-2 co-infection may lead to pneumonia complications oftener than COVID-19 itself ( Madge et al, 2020 , Okoh et al, 2020 ). The ability of HIV/SARS-CoV-2 co-infection to cause excessive T cell activation has been observed in sample sets little in size ( D’Ettorre et al, 2020 , Gao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This second scenario hypothesizes that co-infection with SARSCoV- 2 is more common among PLHIV as suggested by Byrd et al 29 The possibility of virus infection was due to the frequent contact of these participants with hospital settings, which increased the potential risk of exposure to the virus. 30 Indeed, Alharbi et al found a seroprevalence of SARS-CoV-2 of 24.24% among healthcare workers. 25 Antiretroviral treatment of PLHIV may also have had an effect in the asymptomatic presentation of COVID-19 in these infected subjects.…”
Section: Discussionmentioning
confidence: 99%